AGE DETERMINATION AND PALAEOGEOGRAPHIC RECONSTRUCTION OF PINDOS FORELAND BASIN BASED ON CALCAREOUS NANNOFOSSILS - Vakalas, I.; Ananiadis, G.; Kontopoulos, N.; Stoykova, K. K.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2018)
The study area is part of the Pindos foreland (Underhill, 1985). Pindos foreland is a tertiary turbiditic foreland basin fill trending parallel to the external Hellenides and occupies Gavrovo and Ionian isopic zones (Aubouin, 1959). The age of Pindos foreland sediments is still a matter of discussion. B.P. (1971) proposed an early Miocene to middle Miocene age, explaining the presence of Oligocene fauna as a product of large scale erosion and reworking of older sediments during Miocene. IGSR&IFP(1966) suggested a late Eocene to early Miocene age for the basin fill while Fleury (1980), Leigh (1991), Wilpshaar (1995), Bellas (1997) assigned an Oligocene age. Avramidis et al (1999) proposes a middle Eocene to early Miocene age assessment, using nannofosil zones from three studied cross sections in the Klematia-Paramythia basin (middle Ionian zone). The determination of the sediment ages was based on the study of calcareous nannofossils, which came from almost 120 samples covering 11 geological cross sections. The nannofosil marker species that were found in the samples were classified using the biozones proposed by Martini in 1971. According to the age assessments arose from the studied samples, clastic sedimentation in the study area began in the Middle Eocene, with small differences among the basin. The end of clastic sedimentation seems to be at different times in different parts of the basin.